ĐKXĐ: \(x\ge1;y\ge0\)
\(xy+x+y=x^2-2y^2\Leftrightarrow x^2-\left(y+1\right)x-2y^2-y=0\)
\(\Delta=\left(y+1\right)^2+4\left(2y^2+y\right)=\left(3y+1\right)^2\)
\(\Rightarrow\left[{}\begin{matrix}x=\frac{y+1+3y+1}{2}=2y+1\\x=\frac{y+1-3y-1}{2}=-y\le0< 1\left(l\right)\end{matrix}\right.\)
Thay \(x=2y+1\) vào pt dưới:
\(\left(2y+1\right)\sqrt{2y}-3\sqrt{2y}=2\left(2y+1\right)-2y\)
\(\Leftrightarrow\left(2y-2\right)\sqrt{2y}=2y+2\)
Đặt \(\sqrt{2y}=a\ge0\Rightarrow\left(a^2-2\right)a=a^2+2\)
\(\Leftrightarrow a^3-a^2-2a-2=0\)
Đến đây ko biết giải kiểu gì :(
cậu viết thế nào thế bảo cho mk vs